Role of platelet-rich plasma in treatment of knee osteoarthritis - Ismail A Yassin; Faisal H Zayed; Ahmed F Abd El-Aziz; Mahmoud K Beltagy (Wolters Kluwer Medknow Publications, 2020)
Background Osteoarthritis (OA) is a degenerative joint disease of multifactorial etiology and affects synovial joints. The risk of developing OA substantially increases with each decade after the age of 45 years. It is characterized by progressive deterioration and loss of articular cartilage with structural and functional changes in the entire joint, including the synovium, periarticular ligaments, and subchondral bone. Objective To assess the clinical effects of intra-articular injection of platelet-rich plasma (PRP) into the knee joint with mild to moderate OA regarding pain, quality of life, and return to activity. Patients and methods The study included 30 patients in the age range of 30-70 years complaining of knee OA grade II and III based on Kellgren and Lawrence classification and confirmed by radiographs. The patients received three intra-articular PRP injections with weekly intervals. Results A statistically significant improvement in the joint function was observed after 6 months according to the Western Ontario and McMaster Universities Osteoarthritis Index scoring index. Conclusion From the results of our study, intra-articular PRP injection is considered as a safe and low-cost line of knee OA treatment with few adverse effects.